2007
DOI: 10.1007/s11205-007-9153-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic Differences in Self-reported Psychological Distress Among 25- to 64-Year-Old Finns

Abstract: Psychological distress, Socio-demographic differences, Education, Employment status, Family status,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
2
24
0
4
Order By: Relevance
“…No grupo dos que vivem sem companheiro, geralmente, os recursos econômi-cos são insuficientes, a integração social é mais fraca e a percepção do sentido da vida é mais negativa do que entre aqueles que dividem a vida com alguém 28 . Todos esses fatores provavelmente exerceram um papel na diminuição das chances de ingresso e manutenção do emprego.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No grupo dos que vivem sem companheiro, geralmente, os recursos econômi-cos são insuficientes, a integração social é mais fraca e a percepção do sentido da vida é mais negativa do que entre aqueles que dividem a vida com alguém 28 . Todos esses fatores provavelmente exerceram um papel na diminuição das chances de ingresso e manutenção do emprego.…”
Section: Discussionunclassified
“…Similarmente, os participantes com histórico de internação durante a vida tiveram menos chance de informar inserção no trabalho. É possível que prejuízos na esfera da formação e da socialização tenham enfraquecido a construção de habilidades técnicas e competências sociais muito valorizadas no atual mercado de trabalho 27,28,29 . O estigma geralmente produzido quando o sujeito se submete a internações psiquiátricas é mais um fator a ser considerado na interpretação dos resultados descritos.…”
Section: Discussionunclassified
“…However, the interactions between age and employment status and between birth cohort and marital status are no longer statistically significant in men when employment status, marital status and education are taken into account together. Several studies have shown that non-employment (Marchand et al 2012;Matthews et al 2001;Talala et al 2007;Walters et al 2002), being without a spouse (Marchand et al 2012;Matthews et al 2001;Talala et al 2007) and low educational level (Mandemakers and Monden 2010;Talala et al 2007;Walters et al 2002) are associated with psychological distress. To our knowledge, no studies have compared the effect of these variables on psychological distress in different age groups.…”
Section: Effect Of Covariates On the Age Distribution Of Psychologicamentioning
confidence: 99%
“…Correlations between SES and sleep disturbance have been documented in diverse mixed gender groups such as US community dwelling older adults (Hall, Buysse, & Nofzinger, et al, 2008) and New Zealand Maori and non-Maori adults (Paine, Gander, Harris, & Reid, 2004). Employment status was found to be associated with insomnia in Finnish men but not women (Talala, Huurre, Aro, Martelin & Prattala, 2008).…”
Section: Introductionmentioning
confidence: 99%